Performances of GAGAN Satellite-Based Augmentation System in Thailand Region - Sophan, Somkit; Phakphisut, Watid; Myint, Lin M.M.; Supnithi, Pornchai (My University, 2020)
The ASEAN IVO project currently supports the research related to GNSS and ionospheric data products for disaster prevention and aviation in low-latitude regions. Satellite-Based Augmentation System (SBAS) is vital to air navigation in many regions around the world. In Thailand, the L1-frequency SBAS corrections can be received from the GPS Aided Geo Augmented Navigation (GAGAN) system which is intended for use over Indian airspace. In this work, we analyze the performances of the GAGAN system in Thailand on quiet and disturbed days in March 2019 by applying the entire corrections received at King Mongkut's Institute of Technology Ladkrabang station. The 95-percent horizontal and vertical accuracies on quiet days are 1.52 and 3.18 meters, respectively. In contrast, on disturbed days they are 1.97 and 3.41 meters, respectively.
Keywords: GAGAN; GPS; SBAS; SPP